BEYOND ISLAM-MALAY: Hegemony, Exclusion, and Decolonial Resistance in Riau - Hanafi, Imam; Wan Yusoff, Wan Zahari bin (Asia-Pacific Journal on Religion and Society, 2023)
The narrative of “Islam is Malay, and Malay is Islam” has become a dominant identity construct in Riau. This article unpacks how such a narrative operates as a hegemonic discourse that excludes non-Muslim Indigenous communities—such as the Akit, Talang Mamak, and Anak Rawa peoples—from being recognized as part of the "Malay group." Drawing on Michel Foucault’s theory of power-knowledge and decolonial approaches in religious studies, this research reveals mechanisms of exclusion through language, cultural policy, and the distribution of resources—all of which privilege the dominant identity. At the same time, Indigenous communities engage in cultural resistance through silence, concealed spiritual practices, and adaptive identity strategies. This article calls for a re-reading of Malay identity through a more pluralistic and inclusive lens, and proposes a decolonial framework as a pathway toward representational and cultural justice in the Riau region.